2012
DOI: 10.1007/978-3-642-34752-8_23
|View full text |Cite
|
Sign up to set email alerts
|

Design and Architecture of a Novel Preservation Watch System

Abstract: Successful preservation of content requires sophisticated mechanisms for collecting, tracking and analyzing information about a multitude of relevant aspects. This is not limited to content itself, but also tracking of available software, other organization's content, usage statistics and trends, format risks, systems operations and many more. Such tracking requires a flexible system that supports evolution over time and provides an extensible platform for scalability. This article presents a novel approach to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Whereas emulation was the least practiced strategy (5.8%). Similarly, out of 342 organizations surveyed by Faria (2017) in different countries also reported that most of them were backing up their digital materials. Above half (51%) claimed to be monitoring backup failure.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas emulation was the least practiced strategy (5.8%). Similarly, out of 342 organizations surveyed by Faria (2017) in different countries also reported that most of them were backing up their digital materials. Above half (51%) claimed to be monitoring backup failure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of surveys have been conducted on digital preservation in different parts of the world. The plotting confirms that studies have been conducted covering institutions worldwide (Atkins et al ., 2017; Bergau, 2010; Bergin, 2013; Engelhardt, 2013; Faria, 2017; Hedstrom and Montgomery, 1998; OCLC/RLGPREMIS Working Group, 2004; Sinclair et al. , 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scout [25] is an automated preservation monitoring service which supports the scalable preservation planning process by collecting and analyzing information on the preservation environment, pulling together information from heterogeneous sources and providing coherent unified access to it. It addresses the need to combine an awareness of the internal state of an organization and its systems (internal monitoring) with an awareness of the environment in the widest sense (external monitoring) to enable a continued assessment of the alignment between the two (Faria et al, 2012).…”
Section: Scout: Scalable Monitoringmentioning
confidence: 99%
“…Once information is collected, it is saved in a formally specified and normalized manner to the knowledge base (Faria et al, 2012). Built upon linked data principles, the knowledge base supports reasoning on and analysis of the collected data using standard mechanisms such as SPARQL [27].…”
Section: Scout: Scalable Monitoringmentioning
confidence: 99%
See 1 more Smart Citation